Association of blood lipid profile with incident chronic kidney disease: A Mendelian randomization study. (May 2020) - Zhang, Yan-Bo; Sheng, Li-Ting; Wei, Wei; Guo, Huan; Yang, Handong; Min, Xinwen; Guo, Kunquan; Yang, Kun; Zhang, Xiaomin; He, Meian; Wu, Tangchun; Pan, An
Abstract: Background and aims: Cohort studies found blood lipid traits were associated with the risk of chronic kidney disease (CKD). We aimed to investigate whether blood lipid traits were causally associated with the risk of CKD in the Chinese. Methods: 15, 244 participants without kidney disease and cancer from the Dongfeng-Tongji cohort were recruited in 2008–2010 in Shiyan City, China. Blood total cholesterol (TC), high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c), and triglyceride (TG) levels were measured. 5251 participants had genotype data and were included in the Mendelian randomization analysis. Incident CKD was defined as estimated glomerular filtration rate <60 ml/min per 1.73 m 2 in 2013. Logistic regression and Mendelian randomization methods were used to estimate the observed and causal associations of blood lipid traits with incident CKD. Results: Various blood lipid traits were associated with CKD risk, and the odds ratios (95% confidence intervals) for incident CKD comparing the extreme quartiles were 1.45 (1.24–1.70) for TG, 1.26 (1.08–1.46) for nonHDL-c, 2.21 (1.91–2.57) for TC:HDL-c ratio, 2.14 (1.83–2.51) for TG:HDL-c ratio, and 0.47 (0.40–0.55) for HDL-c. The Mendelian randomization analysis indicated that 1 mmol/l increase in the genetic predicted blood TG level was associated with a 5% (95% confidence interval, 0–10%) higher risk of CKD. Conclusions: Although blood levels of HDL-c, TG, nonHDL-c, TC:HDL-c ratio, and TG:HDL-c ratio were observed to be associated with incident CKD, the Mendelian randomization analysis provided genetic evidence to support causal relation for blood TG level only. Graphical abstract: Image 1 Highlights: Whether blood lipid is causally related to the risk of chronic kidney disease (CKD), especially in the Chinese, is unclear. The relation of blood lipid with the risk of CKD was prospectively investigated in 15, 244 Chinese. The top quartile of blood TG was related to a 45% higher risk of CKD compared with the bottom quartile. Blood nonHDL-c, HDL-c, TC:HDL-c, and TG:HDL-c were related to the risk of CKD. Mendelian randomization showed 1 mmol/l increase in blood TG was related to a 5% higher risk of CKD.